The mediating effect of innovativeness on innovation strategy, atmosphere, culture and organizational performance: Proposed theoretical framework - Phankhong, Thienchai; Abu Bakar, Lily Julienti; Poespowidjojo, Donny Abdul Latief (2017)
This study aims to propose the theorethical framework of “The Mediating Effect of Innovativeness on The Relationship between Innovation Strategy, Atmosphere, Culture and Performance of Hospitality Industry in Thailand”.The primary data will be gathered through a questionnaire survey send 254 hotel executive at three to five star rating hotels in Thailand.This study will offer clarity on the mediating effect of innovativeness on the relationship between innovation strategy, organizational atmosphere, organizational culture and performance of hospitality industry in Thailand.The significance of this study will support to the government and the relevant organizations in proposing policies related to improving and developing hospitality industry performance in Thailand.Furthermore, the finding will be contribute for the owner manager and executive of hotel to better understanding the key factors that should be encouraged in order to improve firm performance and factors that should be avoided.The study will also contributes to the theory development the Resource-Based View and Dynamic Capabilities (DC).